Anticorruption in transition 3 : who is succeeding ... and why? - Anderson, James Horton 1964-; Gray, Cheryl Williamson 1954- (Washington, DC : The World Bank, 2006)
This is the third in a series of World Bank studies that examines patterns and trends in corruption in business-government interactions in the transition countries of Europe and Central Asia. The message of this series is positive: Corruption has fallen since 2000 in many transition countries in the region. Firms are paying bribes less frequently and in smaller amounts (as a share of reveneues) than in the past, and they see corruption as less of a problem for business. Reforms have accelerated in the past decade. Many countries are cutting red tape, simplifying taxes, and strengthening audits. These reforms are translating into lower levels of corruption in areas such as tax and customs administration, business licensing, and inspections. While the impetus for reforms and their design and implementation vary across countries, the link between reform and results is unmistakable. There is no room for complacency, however. Corruption is not falling in all countries or all sectors, and even the most successful reformers still tend to have higher levels of firm-level corruption than in Western Europe. The burden weighs most heavily on the new private firms that are the engine of growth and employment in the region. And even in countries that are showing success, the gains are not irreversible. Leaders need to continue to open their economic and political systems to greater competition, foster transparency and accountability in the public sector, and reduce administrative and regulatory burdens for firms.
Keywords: CORRUPCIÓN POLÍTICA -- EUROPA; CORRUPCIÓN POLÍTICA -- ASIA CENTRAL; PRIVATIZACIÓN -- PRÁCTICAS CORRUPTAS -- EUROPA; PRIVATIZACIÓN -- PRÁCTICAS CORRUPTAS -- ASIA CENTRAL